Penerapan Algoritma Convolutional Neural Network dan Haar Cascade Untuk Presensi Dengan Video Rekaman Zoom - Muhammad Verdiansyah; Achmad Solichin (Jurnal Ilmiah Informatika, 2022)
The COVID-19 pandemic that is engulfing the world is one of the situations that urges the use of and even human dependence on technology to become higher. This pandemic that can cause death by spreading through droplets or water droplets, so many countries have implemented social restrictions by prohibiting their citizens from doing many activities outside. The use of technology such as the Google Meet and Zoom applications has become a new habit for the community, especially in learning and teaching. Attendance is important to know and control the presence of students in the teaching and learning process. Currently, attendance at online lectures is still mostly done by calling students one by one or asking students to fill out certain forms. It has weaknesses and is less effective. Therefore, this study proposes presence with face identification using a web-based application system. The method used in this research are Haar Cascade face detection for facial image extraction and Convolutional Neural Network (CNN) algorithm for face identification process. The contribution given from this research in the form of identification can be done using video recordings of zoom and images or screenshots from zoom and displaying student attendance. In this study, the dataset was sourced from taking photos directly on individuals. There are 20 labels used in this study. The identification results of 1119 facial images (test data) on the CNN custom model, obtained 88% accuracy, 88% precision, and 83% recall.